Intercultural Communication in the Public Discussion with the Modern Royal Javanese Princesses - Nindita Nilasari (Linguistic Community Services Journal, 2024)
Current crosscultural communication and intercultural communication discipline include more theories such as increasing focus on studying the intercultural in different contexts and increasing debate as to what is intercultural itself. Today transformation of the media landscape for instance ranks of radio microphones as blogs, were replacing one-to-many voices of a mass medium with a broader range of voices. There is an ongoing existence of keraton, including their family play a significant role in society, this article aimed to reveal intercultural linguistics characteristic communications of modern Javanese women. Study shows that modern Javanese princesses applied some communication strategies such as the use of indirect pronouns, metaphorical expressions, and another repair of interlocutors. Most interestingly, the princess did not hesitate to express her true feelings in terms of speaking up today women's mindset is still limited by patriarchal values in general society.